Low-Cost Domestic Grey Wastewater Treatment and Recycling System. - Mubangizi, Paul Steven (Kabale University, 2024)
This report explored the development and evaluation of a low-cost domestic wastewater treatment system designed for small communities. The primary objective is to assess the effectiveness of using locally available materials and simple technologies to treat domestic wastewater efficiently. The study focuses on a combination of physical, chemical, and biological treatment methods, including sand filtration, constructed wetlands, and ceramic filter bioreactors. Data were collected over six months, analyzing parameters such as biochemical oxygen demand (BOD), chemical oxygen demand (COD), total suspended solids (TSS), and nutrient levels. The research Results demonstrate that the integrated approach significantly reduces contaminants, achieving compliance with local environmental standards. The system’s low cost and ease of maintenance make it a viable option for under-resourced areas. In conclusion, the findings highlight the potential of low-cost, decentralized wastewater treatment systems to provide sustainable and effective solutions for domestic wastewater management. Recommendations for further improvements and areas for future research are also discussed.